2011
DOI: 10.3354/meps09198
|View full text |Cite
|
Sign up to set email alerts
|

Grouper and snapper movements and habitat use in Dry Tortugas, Florida

Abstract: Home ranges, activity patterns, and habitat preferences in and around no-take marine reserves (NTMRs) were evaluated for 5 exploited snapper-grouper species in diverse coral reef habitats in the Dry Tortugas, Florida. Movements of ultrasonic tagged reef fish were determined using a calibrated array of omnidirectional hydroacoustic receivers. Average home range sizes were 2.09 ± 0.39 km 2 (n = 28; total length, TL = 45 to 66 cm) for red grouper Epinephelus morio, 4.17 ± 1.75 km 2 (n = 5, TL = 48 to 55 cm) for y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
96
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 48 publications
0
96
1
Order By: Relevance
“…Excess zeroes could have occurred if individual fish inhabiting a PSU moved into or out of the SSU, lowering the probability of their being observed by a diver. While many reef-associated fishes tend to exhibit low mobility, larger grouper species maintain home ranges considerably larger than the 200-m × 200-m PSU (Chapman and Kramer 2000;Farmer and Ault 2011). The areal extent of an SSU in relation to that of a PSU also suggests that finescale spatial environmental heterogeneity could influence the propensity for not being observed by divers.…”
Section: Discussionmentioning
confidence: 99%
“…Excess zeroes could have occurred if individual fish inhabiting a PSU moved into or out of the SSU, lowering the probability of their being observed by a diver. While many reef-associated fishes tend to exhibit low mobility, larger grouper species maintain home ranges considerably larger than the 200-m × 200-m PSU (Chapman and Kramer 2000;Farmer and Ault 2011). The areal extent of an SSU in relation to that of a PSU also suggests that finescale spatial environmental heterogeneity could influence the propensity for not being observed by divers.…”
Section: Discussionmentioning
confidence: 99%
“…Farmer & Ault (2011) reported that L. analis makes short, frequent (scales of minutes) movements of up to 500 m, and Lindholm et al (2005) showed that Ocyurus chrysurus also regularly moved back and forth from sites 500 m apart at 15 min intervals. As all 3 lutjanids appear to display similar movement abilities, differences in observed correlations between sampling methods may be affected by schooling behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These spatial and temporal scales of study may be suffi cient for elucidating the size of the home range of relatively sedentary fi shes that inhabit restricted areas, such as coral reefs. However, recent work indicates that estimates of home range may be larger when habitat use of a target fi sh is monitored over larger spatial scales and over longer time periods (Farmer and Ault, 2011). Furthermore, because movement behaviors may vary among individuals, large sample sizes could improve our understanding of the size of the home range for a given species.…”
mentioning
confidence: 99%
“…Home range and movements of mobile species can be assessed with acoustic telemetry (e.g., Dawson and Starr, 2009;Douglas et al, 2009;Meyer et al, 2009;Farmer and Ault, 2011;Knip et al, 2012 intensive information, many acoustic studies of the home ranges of fi shes have been conducted on relatively small spatial scales (hundreds of meters to a few kilometers) or during brief periods of time (days to weeks) with few fi sh (typically 15 or less). These spatial and temporal scales of study may be suffi cient for elucidating the size of the home range of relatively sedentary fi shes that inhabit restricted areas, such as coral reefs.…”
mentioning
confidence: 99%